The Urgency of Policy-Making Through Village Regulations about Waste Management in Purwosuman Village - Qoiri, Mutmainah Nur (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2025)
This research analyzes the urgency of village-level waste management policies in Purwosuman Village, Sragen. The practices of dumping waste into rivers, landfilling and burning waste pose risks to the environment and human health. Notwithstanding the profound implications of these behaviours, they have not been perceived as deviations by the perpetrators or the surrounding community. The objective of this research is to examine the significance of establishing Village Regulations pertaining to waste management, with a particular emphasis on the underlying causes of the practices of burning waste and dumping waste into the river. The research method employed is a normative-empirical and socio-legal approach through a sociological case study in Purwosuman Village and the potential for regulation through village legal products. The findings indicated that Purwosuman Village is lacking in infrastructure, including waste banks, waste disposal sites (TPS), subscription waste transportation services, and even Village Regulations, which serve as a legal foundation for waste management. In conclusion, it is imperative that village-based regulations are established as a legal framework, in addition to community education efforts and the implementation of related infrastructure development.